2012
DOI: 10.1021/bc2006219
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Specific siRNA Delivery Using Antibody-Conjugated Chitosan Nanoparticles

Abstract: The intracellular delivery of small interfering RNA (siRNA) plays a key role in RNA interference (RNAi) and provides an emerging technique to treat various diseases, including infectious diseases. Chitosan has frequently been used in gene delivery applications, including siRNA delivery. However, studies regarding the modification of chitosan with antibodies specifically targeting T cells are lacking. We hypothesized that chitosan nanoparticles modified with T cell-specific antibodies would be useful for delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…On the other hand, electroporation is not a suitable method for in vivo administration of siRNA [18]. Various delivery systems have been discovered to target T cells, including CD3 targeted polyethylenimine (PEI) [19], CD40L targeted liposomes [20], CD7 targeted chitosan [21] or oligo-arginine [22]. However, their efficiency and potential systemic side effects for asthma therapy remain to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electroporation is not a suitable method for in vivo administration of siRNA [18]. Various delivery systems have been discovered to target T cells, including CD3 targeted polyethylenimine (PEI) [19], CD40L targeted liposomes [20], CD7 targeted chitosan [21] or oligo-arginine [22]. However, their efficiency and potential systemic side effects for asthma therapy remain to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a copolymer of D-glucosamine and N-acetyl glucosamine derived from chitin. It was reported that chitosan and its derivant carboxymethyl chitosan (CMC) are potentially useful pharmaceutical materials owing to their good biocompatibility and low toxicity [10][11][12]. Tu et al [13] reported the swelling kinetics of a series of carboxymethyl chitosan-g-poly (acrylic acid) hydrogels pretreated under acidic or neutral media for applications in colon-specific drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, Cs NPs, obtained by different methodologies [24] (covalent cross-linking, precipitation, self-assembly, spraydrying and ionic cross-linking with tripolyphosphate), were employed in targeted therapy for colon or mucosal delivery [25], cancer treatment [26], or in delivering of vaccines, genes and peptides [27]. Moreover, as Cs NPs are unstable in the bloodstream owing to the activation of the reticuloendothelial system, PEGylation of Cs NPs surface is strongly required [28].…”
mentioning
confidence: 99%